The language of sustainability - architecture in the construction of a sustainable society - Matteucci, Magda Beatriz de Almeida; Vera, Rosângela (Technical and Scientific Journal Green Cities, 2024)
The language of sustainable development has covered up the concrete causes of the environmental crisis. The expression “sustainable development” has become mandatory in research or extension projects, suggesting a definitive solution to a given problem. Development must include scientific knowledge produced by the modern world, however, the community must make the decision to adopt a technology. The purpose of the study was to list ways in which architecture, through sustainable actions, can contribute to the conservation and restoration of quality of life to bequeath it to future generations. In the study, a dynamic was used in the Ecology discipline of the Architecture and Urbanism course/UFG. 27 students participated. The most relevant suggestions were: solar and wind renewable energy sources (5.24%), rainwater capture and water reuse systems (5.24%); green roofs with 4.29%, ensure natural ventilation, use of high-efficiency luminaires, LED/PL and design considering the maximum number of green spaces (3.81%). Other suggestions were taking advantage of natural lighting (3.33%); build considering the environmental life cycle and use of wood certified with the Green Seal/recycled both with (3.10%) and materials and components that respect environmental legislation and have a longer useful life as well as the use of paints that represent alternatives less toxic/natural, both with 2.38%. The results indicate that there are tendencies to take actions that contribute to reducing the impact of human actions on nature and, consequently, a more sustainable world
Keywords: Ecodevelopmen; Light technologies; Sustainable solutions; Ecoarchitecture